Individual counseling using Rational Emotive Behavior Therapy (REBT) techniques to increase confidence students in learning - Fardhatul Riani Putri; Yeni Karneli (Current Issues in Counseling, 2021)
Self-confidence plays an important role in the learning process at school because with the emergence of self-confidence in students, all the potential possessed by students can be maximally developed, this is because it is supported by confidence, belief in students' attitudes towards their abilities so that they are able to perform well in the field of education. academic, non-academic and social environment in which they are located. The self-confidence that students have makes them feel capable of achieving achievements in school because students have confidence in their abilities. The research method used is an experimental research method. As for the research design, the researcher used a pre-experimental method with the type used was a one-group pretest-posttest design. Using an experimental quantitative approach. In this study, students of class X had low self-confidence. Based on the findings above, it can be concluded that self-confidence can be increased through individual counseling services with a rational emotive behavior therapy (REBT).